PENGARUH INDEPENDENSI DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN (Faletehan Jurnal Ekonomi dan Bisnis, 2024)
This research aims to determine the effect of independence and audit quality on the integrity of financial reports. The independent variables in this research are independence and audit quality, while the dependent variable is the integrity of financial reports. The research method in this research is quantitative, expressed in numbers and the calculations use statistical methods with software. The population includes food and beverage sub-sector manufacturing companies listed on the IDX in 2015-2019. The sampling technique used was purposive sampling. From the calculation results, all classical assumption tests have been fulfilled. The partial research results show that independence has an effect on the integrity of financial reports with a significant value of 0.011 < 0.05 and audit quality has no effect on the integrity of financial reports with a significant value of 0.218 > 0.05. Meanwhile, the research results simultaneously show that independence and audit quality together influence the integrity of financial reports with a significant value of 0.037 < 0.05.